The structure of the poetic image of lamentations (poetry of the age of prophecy) - عدنان محمود, تغريد; عواد أرحيم, إبراهيم (Al-Adab Journal, 2018)
The artistic image is the hallmark of the poetic discourse, the borderline between the language of poetry and the language of prose, one of the important pillars on which the creative process is based. However, each image appears only on the basis of the metaphorical expression that occurs in the context of linking the semantics between words and meaning, truth and imagination. The secret of the success of the work of art is that it stems from the text itself and its technical tools, that is, the aesthetic of the text reflects the aesthetics of the poet himself, and his ability to convey his experience and passion to the recipient . This study attempts to stand at the structure of the poetic image in the text - the lamentations of the flags - of the era of prophecy as the main feature of Arabic poetry. In order for the study to reach the desired goal, it is divided into two parts. First, it deals with the concept of the image and its artistic sources, and its impact on the structure of the poetic text . And the other: the formation of artistic image in the structure of poetic text by graphic means , And multiple patterns, including sensory and mental . The metaphor gives power and inspiration to affect the recipient and create a response . We will illustrate these structures through various practical models of lamentation in the age of prophecy .